The finite element analysis of collapse loads of single-spanned historic masonry arch bridges (Ordu, Sarpdere Bridge). (February 2018) - Aydin, Abdulkadir Cüneyt; Özkaya, Suat Gökhan
Abstract: The current methods used in estimating the collapse loads of masonry arch bridges have been examined, and a study has been made aiming the calculation of the behaviors of the single-spanned masonry arch bridges shows under certain loads with the method of static analysis. The model used for the study was 3D formed with the ANSYS package program, and the results of the analysis were achieved using this program, as well. The model that was created was obtained by using the original dimensions of the historical Sarpdere Bridge located within the province of Ordu. The results obtained have shown compliance with the existing studies in the literature. In addition, the effects of the loads on the bridge that were applied to the different places on the system were examined, and the behaviors of the single-span masonry arch bridges under the loads applied were evaluated. The filler and sidewalls on left and right sides of the arch bridge were differentiated the loading about 10%. Highlights: Failure load of historic masonry arch bridge Maximum loading capacity The behavioral acts of masonry arch Deformed shape of finite element model